Lasting immune memory against hepatitis B following challenge 10–11 years after primary vaccination with either three doses of hexavalent DTPa-HBV-IPV/Hib or monovalent hepatitis B vaccine at 3, 5 and 11–12 months of age - Avdicova, Mária; Crasta, Priya D.; Hardt, Karin; Kovac, Martina (Vaccine, 2015)
•10–11 years after DTPa-HBV-IPV/Hib vaccination, 48.4% maintained anti-HBs ≥10mIU/ml.•10–11 years after DTPa-IPV/Hib+HBV vaccination, 58.4% maintained anti-HBs ≥10mIU/ml.•DTPa-HBV-IPV/Hib induced immune memory similar to monovalent HBV-primed subjects.•Duration of protection is likely similar after DTPa-HBV-IPV/Hib and monovalent HBV.•The HBV challenge dose was well tolerated and had an acceptable safety profile. The combined hexavalent diphtheria–tetanus–pertussis–hepatitis B-inactivated poliomyelitis – Haemophilus influenzae type b conjugate vaccine (Infanrix hexa™; DTPa-HBV-IPV/Hib: GlaxoSmithKline Vaccines) induces robust responses to the HBV component when administered at 3, 5 and 11–12 months of age. We assessed long term HBV antibody persistence 10–11 years after primary vaccination in infancy. Antibody persistence and immune memory were assessed post-primary vaccination at 3, 5, 11–12 months with DTPa-HBV-IPV/Hib, or monovalent HBV vaccine (Engerix™ B, GlaxoSmithKline Vaccines) co-administered with DTPa-IPV/Hib (Infanrix™-IPV/Hib, GlaxoSmithKline Vaccines) in 185 children aged 11–12 years. Blood samples were collected before and 1 month after a challenge dose of Engerix™ B (10μg dose). 10–11 years after primary vaccination the percentage of subjects with persisting anti-HBs antibody concentrations ≥10mIU/ml was 48.4% in the DTPa-HBV-IPV/Hib group and 58.4% in the DTPa-IPV/Hib+HBV group. After the HBV challenge dose, the percentage with anti-HBs ≥100mIU/ml increased from 14.7% to 93.6% in the DTPa-HBV-IPV/Hib group and 19.1% to 94.4% in the DTPa-IPV/Hib+HBV group. Anti-HBs GMCs increased by at least 187-fold in each group. An anamnestic response (≥4-fold increase in initially seropositive or anti-HBs concentration ≥10mIU/ml in initially seronegative subjects) was observed in 96.8% and 96.6% of subjects in the DTPa-HBV-IPV/Hib and DTPa-IPV/Hib+HBV groups, respectively. No serious adverse events occurred that were considered related to challenge vaccination. Administration of HBV as part of a combination vaccine or as a monovalent vaccine induced long lasting immune memory against HBV in children primed at 3, 5 and 11 months of age. Antibody persistence and immune memory were similar, suggesting that protection afforded by DTPa-HBV-IPV/Hib and monovalent HBV vaccines, is likely to be of similar duration. The administration of HBV challenge dose 10–11 years after the 3, 5, 11–12 months primary schedule induced strong anamnestic responses and was well tolerated. This study is registered at www.clinicaltrials.gov NCT01138098.